مشكلات الحال الصغرى وأثرها في فهم النص القرآني: دراسة في ضوء نظرية النحو المقامي - الخفاجي، تومان غازي حسين (جامعة القادسية - كلية التربية, 2023)
ترجع أهمية البحث إلى فهم النص القرآني بطريقة أعمق مما هو عليه الآن، وذلك عند حل مشكلات جملة الحال الكبرى وهي: مشكلة تعريف الحال في النحو التقليدي، الذي ولد مشكلتين أولاهما: مشكلة الحال الثابتة، بخلاف التعريف الذي يؤكد أنها متحولة أبدا؛ لأن النحويين لم يضعوا تقنيات تحليل تعيد الحال المتحول منها المحذوفة، ومسرحها إما أن يكون الحس أو الظن، وثانيتهما: الحال الماضوية والمستقبلية، بخلاف التعريف الذي يؤكد أنها حالية أبدا؛ لأنهم جعلوا الزمن الخارجي في الجملة: (أمس، غدا)، مسؤولا عن إنتاج تقسيمات مغلوطة. أما المشكلات الصغرى فهي أربعة خُصصت لها أربعة مباحث، وقد توصل البحث إلى حلها باستعمال المنهج التداولي، عن طريق بيان أن الحال بهيأة الجار والمجرور لا يقدر بـ (مستقر)، لأن حرف الجر يدخل على المصدر وهو حدث وليس ظرفا، ولا تأتي الحال من المبتدأ، فما ظن أنه مبتدأ هو فعل بهيأة الاسم؛ لأنه يرفع فاعلا؛ لذلك تحلى الحال بـ (ال) التي هي للجنس للتنكير لا للتعريف، والحال لا تأتي معرفة، ولا تأتي فضلة؛ لأنها خبر ثان وقد تأتي خبرا وحالا في وقت واحد. The importance of the research is due to understanding the Quranic text in a deeper way than it is now, when solving the problems of the major adverb sentence, which is major problems, which is the problem of defining the adverb of the traditional grammarians, which generated two problems, the first of which is: the problem of the fixed adverb, in contrast to the definition that asserts that the adverb is a never-changing adjective, and is always present; because they did not develop analytical techniques that restore the transformed state of the omitted ones, and its stage is either sense or conjecture, and their second: the past and future states, unlike the definition that confirms the ever present state; because they envisioned the appearance of the external time in the sentence: (yesterday, tomorrow), making the sentences past and future. As for the minor problems, they are four, for which four topics are devoted, and the research has reached its solution, by stating that the case in the form of the dative and the dative is not estimated as (stable), because the preposition enters the infinitive and it is an event and not an adverb, and the adverb does not come from the subject, so what did he think that it is a beginner is a verb in the form of a noun; Because it elevates a subject, so it is adorned with (the) which is for the genus, not for definition, and the condition does not come to know, and does not come to a plus; Because it is a second news and it may come news and adverb at one time What is true is the story of the past and the future. I used the pragmatic approach to solve these problems.
Keywords: النحو العربي -- جمل الحال -- إعراب القرآن